VD_FINDINFO Arrêt / 2022 / 189 vom 24. März 2022 - VD Tribunal cantonal (2022)
RENTE D'INVALIDITÉ, ÉVALUATION DE L'ATTEINTE À LA SANTÉ, RÉVISIONPRESTATION D'ASSURANCE | 17 LPGA, 6 LPGA, 7 LPGA, 8 LPGA